2015
DOI: 10.1038/ejcn.2015.206
|View full text |Cite
|
Sign up to set email alerts
|

Stents in patients with esophageal cancer before chemoradiotherapy: high risk of complications and no impact on the nutritional status

Abstract: Preoperative chemoradiotherapy is the standard of care for locally advanced esophageal cancer, causing persistent deterioration in the nutritional status. We performed a prospective study to evaluate the safety and efficacy of esophageal double-covered self-expandable metal stents in patients with esophageal cancer before chemoradiotherapy. The nutritional status and dysphagia were prospectively recorded. Eleven patients were included: eight were moderate and three were severely malnourished. After stent place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Allum et al (28) conclude that EC patients with nutritional risk should be given 10-14 days of nutritional support before operation. Several approaches have been used to nutritional support during neoadjuvant therapy including esophageal stenting, jejunostomy or gastrostomy, and nasogastric or nasojejunal feeding (42)(43)(44). These approaches may improve prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Allum et al (28) conclude that EC patients with nutritional risk should be given 10-14 days of nutritional support before operation. Several approaches have been used to nutritional support during neoadjuvant therapy including esophageal stenting, jejunostomy or gastrostomy, and nasogastric or nasojejunal feeding (42)(43)(44). These approaches may improve prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to dysphagia and anorexia, esophagitis and side effects from radiotherapy and chemotherapy compromise oral intake. Therefore, patients with esophageal cancer could have persistent deterioration in nutritional status even after dysphagia is improved by SEMS insertion [24]. PG feeding can be used in patients with dysphagia and head and neck cancer and esophageal cancer to stabilize or improve the patients’ nutritional status [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to oesophageal self-expanding metal stents (SEMS), eight recent studies of demonstrated a risk of 0% significant haemorrhage within 7 days of insertion. [150][151][152][153][154][155][156][157] However, studies including delayed haemorrhage showed a risk of 9% in an RCT comparing small-diameter stents with large-diameter stents and an 8% risk in a large retrospective series of 997 patients. 158 159 Causes of haemorrhage included aorta-oesophageal fistula formation, and continued oozing from tumours.…”
Section: Endoscopic Stentingmentioning
confidence: 99%